2000
DOI: 10.1074/jbc.275.12.8726
|View full text |Cite
|
Sign up to set email alerts
|

The CafA Protein Required for the 5′-Maturation of 16 S rRNA Is a 5′-End-dependent Ribonuclease That Has Context-dependent Broad Sequence Specificity

Abstract: The CafA protein, which was initially described as having a role in either Escherichia coli cell division or chromosomal segregation, has recently been shown to be required for the maturation of the 5-end of 16 S rRNA. The sequence of CafA is similar to that of the N-terminal ribonucleolytic half of RNase E, an essential E. coli enzyme that has a central role in the processing of rRNA and the decay of mRNA and RNAI, the antisense regulator of ColE1-type plasmids. We show here that a highly purified preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
169
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 53 publications
8
169
2
1
Order By: Relevance
“…As primary transcripts in E. coli have a triphosphate group at their 5Ј end and the RNaseE-catalyzed hydrolysis generates downstream intermediates that have a 5Ј-monophosphate group (9), the ability of RNaseE to assess the phosphorylation status of 5Ј ends may ensure that after this enzyme has made the first cut in a primary transcript, it will tend to cut any sites downstream before starting on another intact transcript. The N-terminal half of RNaseE is sufficient to discriminate substrates that have a monophosphate group at the 5Ј end (25,26). There is evidence for "5Ј end dependence" in vivo and it has been suggested that this facet of RNaseE-catalyzed cleavage may contribute to the finding that RNA decay occurs in general without the production of significant levels of intermediates in E. coli (27).…”
Section: Panel A)mentioning
confidence: 96%
See 1 more Smart Citation
“…As primary transcripts in E. coli have a triphosphate group at their 5Ј end and the RNaseE-catalyzed hydrolysis generates downstream intermediates that have a 5Ј-monophosphate group (9), the ability of RNaseE to assess the phosphorylation status of 5Ј ends may ensure that after this enzyme has made the first cut in a primary transcript, it will tend to cut any sites downstream before starting on another intact transcript. The N-terminal half of RNaseE is sufficient to discriminate substrates that have a monophosphate group at the 5Ј end (25,26). There is evidence for "5Ј end dependence" in vivo and it has been suggested that this facet of RNaseE-catalyzed cleavage may contribute to the finding that RNA decay occurs in general without the production of significant levels of intermediates in E. coli (27).…”
Section: Panel A)mentioning
confidence: 96%
“…The mechanism by which the b site within the context of a 9 S transcript is cleaved by RNaseE despite the absence of an upstream G remains to be determined. It is possible that the recruitment of RNaseE is regulated by some secondary structural element(s) (17) as suggested relatively early in the study of RNaseE (1,30) or the distance between susceptible sequences and a monophosphate at the 5Ј end (25). From the above, it can be seen that an understanding of the recognition and hydrolysis of RNA by RNaseE will require a systematic analysis of the contribution of RNA sequence and structure, including the phosphorylation status at the 5Ј end, the multiple domains within the C-terminal half of RNaseE, and the effects of other degradosome component.…”
Section: Panel A)mentioning
confidence: 99%
“…In view of the homology of RNase G to the catalytic domain of RNase E, it is not surprising that they have a similar cleavage site specificity, with both preferring to cut RNA within singlestranded regions that are AU-rich (8,9). Another important property shared by these two endonucleases is their preference for RNA substrates that bear a single phosphate group at an unpaired 5Ј end.…”
mentioning
confidence: 99%
“…Another important property shared by these two endonucleases is their preference for RNA substrates that bear a single phosphate group at an unpaired 5Ј end. Remarkably, such substrates are cleaved by full-length RNase E, N-RNase E, or RNase G more than an order of magnitude faster than otherwise identical RNAs bearing a 5Ј-terminal triphosphate or hydroxyl group, even though cleavage may occur far from the 5Ј end (9)(10)(11). The greater susceptibility of 5Ј-monophosphorylated RNAs to cleavage by these enzymes may help to ensure the rapid degradation of the downstream products of initial endonucleolyic cleavage, which differ from their primary-transcript precursors in being 5Ј-monophosphorylated rather than 5Ј-triphosphorylated.…”
mentioning
confidence: 99%
“…The 5′ end of substrate mRNA dramatically affects its ability to be cleaved by RNase E, with the rate constant for 5′ monophosphate RNA more than an order of magnitude greater than that for RNA with a 5′ triphosphate or 5′ hydroxyl 3,4 . The basis for this 5′ end selectivity became clear from the crystal structure of the homotetrameric catalytic domain 5 , which showed the 5′ monophosphate end is hydrogen bonded into a pocket at the base of an RNA-binding channel.…”
mentioning
confidence: 99%